Penyebab Sedikitnya Pengeluaran Rumah Tangga untuk Konsumsi Kesehatan - Heru Wahyudi; Mega Ayulestari (Goodwood, 2022)
Purpose: This study aims to identify the average and percentage of household health consumption expenditure and factors that affect household health consumption expenditure. Research methodology: To identify the average and percentage of household health consumption expenditure were done statistic descriptively, while the analysis method used to identify the influence of these factors is multiple regression with the method of Ordinary Least Square Method (OLS). Results: The research results showed the average household health consumption expenditure is Rp 335,783 or 13% of all household consumption expenditures and the estimated results show that individually and collectively, the household income, the age of the head of the family, the number of family members, the level of education of the head of the family, and the participation of the family in health insurance have a significant positive effect on household health consumption expenditures. Limitations: This research is limited to the research location and cannot be generalized. Contribution: The results obtained from this study are expected to be one of the references in making policy Allocating greater income for health is a wise thing as an effort to prevent or reduce the impact of disease in the future.